Chaotic image encryption algorithm based on fractal-chaotic dynamic S-box - Ge, Bin; Li, Weifeng (Nonlinear dynamics, 2025)
This paper proposes an image encryption algorithm based on a fractal-chaotic dynamic S-box, aiming at the low flexibility of fractal-disordered matrix design, the complexity of iterative design, and the low information entropy and robustness of encrypted images caused by unreasonable S-box design. Firstly, the 3D-coupled sine-Chebyshev chaotic system is controlled to generate chaotic sequences by the random matrix generator and KeyHex generation key, and the sequences for synchronous scrambling are generated by the 4D-hyperchaotic system, and the initial S-box is obtained by the fraction-Zigzags iteration of a simple initial matrix. Secondly, the chaotic sequence generated by 3D-coupled sine-Chebyshev mapping is used to disarrange the initialized S-box to obtain the fractal-chaotic dynamic S-box. Finally, by using the diffusion sequence generated by the 3D-coupled sine-Chebyshev chaotic system, the scrambling sequence generated by the 4D-hyperchaotic system and the fraction-chaotic dynamic S-box to carry out synchronous S-box replacement scrambling and diffusion operation for the image, Then the chaotic sequence generated by 3D-coupled sine-Chebyshev mapping is used to globally rearrange and diffuse the processed images to obtain ciphertext images. The experimental results show that the algorithm has high security and good robustness.